A Computational Screening on Inhibitability of Piper Betle Essential Oil Chemical Structures against Spike Proteins of Mutated SARS-CoV-2-variants D614G, N501Y, and S477N. Issue 3 (3rd July 2022) - Tu Quy, Phan; Thi Ai My, Tran; Thi Thanh Hai, Nguyen; Bui, Thanh Q.; Tuan Quang, Duong; Thanh Triet, Nguyen; Phuoc Hien, Phan; Thi Ai Nhung, Nguyen
ABSTRACT: Aromatic phenylpropenoids in Piper betle essential oil composition can be promising, leading structures to develop inhibitors toward spike proteins of SARS-CoV-2 variants D614G, N501Y, and S477N. Structural formulae of chemical constituents were referenced from our previous report in the literature. Their quantum properties were determined using density functional theory (DFT). Static inhibitability, hydrogen-bonding interactions, and shape complementarity of the ligand-protein complexes were investigated using molecular docking (MD) simulation. All aromatic phenylpropenoids, eucalyptol (TH1 ), chavicol acetate (TH3 ), eugenol (TH4 ), trans -isoeugenol (TH5 ), and eugenol acetate (TH11 ), are predicted to form stable interactions with their targeted proteins and perform high degree of complementarity toward in-pose geometrical shapes. Regarding each variant, the most stable inhibitory systems are TH3-D614G (DS −11.9 kcal.mol −1 ; 3 hydrogen bonds), TH5-N501Y (DS −12.0 kcal.mol −1 ; 3 hydrogen bonds), and TH11-S477N (DS −12.5 kcal.mol −1 ; 4 hydrogen bonds). Lipinski's rule of five justifies the physiochemical and pharmaceutical compatibility of all studied compounds. The results propose a chemotype for enzyme-inhibiting frameworks while still requiring further verification from relevant theoretical and experimental work. Graphical Abstract: uf0001